2021
DOI: 10.1002/jum.15651
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Global and Regional Circumferential Strain of Abdominal Aortic Aneurysm with Different Size by Speckle‐Tracking Echocardiography

Abstract: Objectives We aimed to use speckle‐tracking echocardiography (STE) to quantify circumferential aortic strain of abdominal aortic aneurysms (AAA) with different size. Methods A total of 87 AAA patients were included. The morphological variables, including aortic maximum diameter (MD), end systolic area (ESA), end diastolic area (EDA), and thickness and area of intraluminal thrombus (ILT), were measured by ultrasound. STE was applied to calculate circumferential strain (CS) at 6 equally divided segments of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…A previous study already demonstrated that global and local strains in the aneurysm sac are independent of the aortic diameter, which is confirmed by the present analysis 4 . However, Li et al characterized the differences between small aneurysm <5.5 cm and large aneurysm >5.5 cm and postulated a significant reduction in global circumferential strain with increasing maximum diameter only in small aneurysms but not in the larger ones 9 . Li et al drew their conclusions from a subgroup analysis and not from a long‐term observation of the same probands as in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…A previous study already demonstrated that global and local strains in the aneurysm sac are independent of the aortic diameter, which is confirmed by the present analysis 4 . However, Li et al characterized the differences between small aneurysm <5.5 cm and large aneurysm >5.5 cm and postulated a significant reduction in global circumferential strain with increasing maximum diameter only in small aneurysms but not in the larger ones 9 . Li et al drew their conclusions from a subgroup analysis and not from a long‐term observation of the same probands as in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…A third ST US study previously reported that AAA peak circumferential strain trended lower with increasing diameters up to 6.5 cm, namely, from 3.89% for AAA <4.5 cm to 2.75% for AAA between 4.5 cm and <5.5 cm, and 1.8% for AAA between 5.5 cm and 6.5 cm. 18 The in vivo AAA strains measured in our study exhibited the same trend with diameter, although with 2.7-fold lower magnitudes than that US study. The consistently larger strain magnitudes of this latter ST US study compared with other ST US studies as well as the present study may be due to the use of a higher frame rate.…”
Section: Discussionsupporting
confidence: 59%
“…Based on a previous aortic DENSE study from healthy adult volunteers, 12 this range would be consistent with aortic strains from the majority of healthy adults over 35 years of age. However, for future applications in the assessment of aortopathies such as aneurysms and dissections, aortic DENSE must quantify focal and/or generalized stiffening that can yield circumferential strains as low as 1%–5% 29–31 . Future tests with improvement in the strength and variability of the phantoms may allow testing over a broader range of strains, including focused evaluations of stiff phantoms with strains <2% to mimic aortopathies and more compliant phantoms with strains ≥10% to mimic young aortas.…”
Section: Discussionmentioning
confidence: 99%